Design of a low-cost mini quadrotor and altitude control using a micro laser sensor. Issue 3 (2nd September 2019) - Kim, JeongHwan; Aurecianus, Steven; Nam, Seonglok; Park, Jungkeun; Kang, Taesam
Abstract : Purpose: The purpose of this paper is to introduce a low-cost quadrotor that can be used for educational purposes and investigate the applicability of a low-cost MEMS laser sensor for accurate altitude control. Design/methodology/approach: A single printed circuit board is designed to form the structure of the quadrotor. A low-cost MEMS motion sensor, a microcontroller and four small motors are mounted on the board. A separate laser sensor module measures the altitude. A remote controller is designed to control the quadrotor's motion. The remote controller communicates with the quadrotor via wireless connection. Roll and pitch attitude stabilization is achieved using the proportional and derivative control algorithm. The applicability of an MEMS laser sensor for altitude control is also studied. Findings: The low-cost quadrotor works well even though its body structure is made using a printed circuit board. Low pass and Kalman filters work well for attitude estimation and control application. The laser sensor is very accurate and good for altitude feedback; however, it has a relatively short measurement range and its sampling rate is relatively slow, which limits its applications. The vertical velocity obtained by differentiating the laser altitude has delay and inhibits suitable damping. Using the vertical velocity obtained by integrating the vertical accelerometer's output, the damping performance is improved. Originality/value: Developing a low-cost quadrotor that can be used for educational purposes and successfully implementing altitude control using a laser sensor and accelerometer.